The development of the effective learning environment by creating an effective teaching in the classroom. - Prameswari, Sanchia Janita; Budiyanto, Cucuk (IJIE (Indonesian Journal of Informatics Education), 2017)
The changes in learning management typically involve the introduction of various alternative learning methods. The development of an effective learning experience requires the modification of conventional learning. Teaching and learning constructively synchronize instructions and assessment toward the desired learning outcomes. Notwithstanding the vast literature on the creation of effective learning, the lack of explanation on how the relationship between effective teaching and effective classroom would likely leave practitioners and academia without a clear guidance on how to operationalize the creation of effective learning in real life. A systematic literature review procedure was conducted upon published papers between 2007 and 2015 in outstanding education journals. This paper contributes to the literature by amassing the knowledge on pedagogical practices in effective learning creation. In addition, to obtain a granular elaboration about the matter, a framework to operationalize the creation of effective learning is suggested. Three aspects compose the framework namely teachers' intrinsic capabilities, educational institution support, and student’s participative involvement. The roles of each party were extracted from the knowledge contained in the reviewed literature. This work is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.